Napoleon's 1796 Italian campaign - Clausewitz, Carl von, 1780-1831 (University Press of Kansas, 2018)
"Prussian general Carl von Clausewitz (1780-1831) is considered one of the greatest military theorists and historians of the modern era. While he is best known for the monumental Vom Krieg (On War), he wrote several other important works, one of which is Der Feldzug von 1796 in Italien (The 1796 Italian Campaign). It was published in 1833, two years after Clausewitz's death. The Italian Campaign was a crucial episode in the wars of the French Revolution and cemented Napoleon's reputation as a military genius, but Clausewitz's history has been relatively neglected, primarily because it has never been translated into English. Murray and Pringle's translation will make accessible in English one of the most important campaigns of the French Revolutionary Wars and will provide students, scholars, and others with a tool for more effective and accurate textual analysis of Clausewitz's theoretical writings"--